2012
DOI: 10.1292/jvms.12-0177
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Diagnostic Color Doppler Ultrasonography in Equine Superficial Digital Flexor Tendonitis

Abstract: ABSTRACT. We hypothesized that semi-quantitative determinations of changeable blood flows in granulation and scar tissues during tendon healing could be helpful for differentiation between the acute phase rich in blood vessels and the remodeling phase with fewer vessels. Ten Thoroughbreds with injured superficial digital flexor tendon (SDFT) in a forelimb were used for evaluation of blood flows in the injured tendons of racehorses using color Doppler (CD) ultrasonography. Using longitudinal CD images, features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…These changes in mechanical properties are expected to alter the deformability and stiffness of tendons . The difference in deformability between diseased and normal tissues must be great enough to be detected with elastography for this to be a clinically useful modality . Through evaluation of injuries of the Achilles tendon in people, there was appreciable softness in acute injuries with gradual increases in stiffness as healing progressed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in mechanical properties are expected to alter the deformability and stiffness of tendons . The difference in deformability between diseased and normal tissues must be great enough to be detected with elastography for this to be a clinically useful modality . Through evaluation of injuries of the Achilles tendon in people, there was appreciable softness in acute injuries with gradual increases in stiffness as healing progressed .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, diagnosis of these injuries is most commonly made via clinical evaluation in combination with gray‐scale ultrasonography. While gray‐scale ultrasound provides important morphologic information and correlates well with histologic and magnetic resonance imaging (MRI) findings, it does not allow evaluation of the mechanical properties of tissues and is incapable of predicting injuries to the superficial digital flexor tendon (SDFT) . The viscoelastic properties of both human and equine tendons and ligaments and their response to stress and strain have been evaluated in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…The role of persistent intra-tendinous vascularization is seen controversial in the literature. Traditionally, persistent vascularization has been interpreted as a sign of inadequate healing and incomplete repair (Kristoffersen et al 2005, Murata et al 2012), but it is not clear in the literature for how many months the vascularization should be visible, so that it can be called persistent. On the contrary, Bosch and others (2011a) reported that 23 weeks after intra-tendinous PRP treatment, the PRP treated tendons presented a higher CDU vascularization score than saline treated tendons.…”
Section: Discussionmentioning
confidence: 99%
“…CD signal was in contrary detected in affected SDFT and suspensory ligament (Kristoffersen et al, 2005). More recently, other authors stated that blood flows appearing on CD images of equine SDFT were indicative of vessels in residual inflammatory granulation tissue replenishing the injured tendon, concluding that CD images could provide another ultrasonographic method for differentiating between inflammatory granulation and hypovascular scar tissues during the remodeling phase of tendon healing (Murata et al, 2012). Power Doppler (PD), unlike CD, is independent of the probe being aligned to the flow and can detect abnormal vascularity in tendons with higher sensitivity compared to CD (Richards et al, 2005).…”
Section: Introductionmentioning
confidence: 98%